Analysis of detection of ecological hazard based on computing the measures of current recurrence of ecosystem states - Pospelov, Boris; Danchenko, Yuliya; Dadashov, Ilgar Firdovsi; Skliarov, Stanislav; Gornostal, Stella; Cherkashyn, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2018)
Analysis of the early detection of an environmental hazard in ecosystems was performed. New measures of the current recurrence of states that allow their use for the early detection of an environmental hazard in ecosystems were proposed. Calculations of the measures under consideration are based on the distribution of the known measure of global recurrence for the case of the calculation of measures of current recurrence in moving square windows. In this case, one of the measures under consideration is based on the implementation of a moving square window along the main diagonal of the recurrent plot of state. Another measure is based on the use of a moving window of the specified size along the horizontal (vertical) axis of recurrence plots. The latter made it possible to obtain a constructive current measure for calculation of recurrence to identify dangerous states in ecosystems based on the temporal localization of zero recurrence of states at minimum sizes of a moving window. In accordance with the proposed measures of current recurrence, the possibilities of using the measures for the early identification of an environmental hazard for gas medium with the ignition center of combustible material, such as alcohol, were analyzed. It was shown that the window measure of current recurrence at a horizontal moving smallsize window is the most suitable of the considered measures. It was found that for such a measure, window sizes must be in the range from 5×5 to 15×15 counts. In this case, the values of region ε of neighborhood for the considered states must be selected in the range from 0.01 to 0.15. It was determined theoretically and experimentally that the specified measure of current recurrence of states with a horizontally moving window can be considered as a structural current measure of recurrence to ensure a reliable early detection of hazardous states in different ecosystems